PERAN SATUAN POLISI PAMONG PRAJA (SATPOL PP) DALAM PENGAWASAN PEREDARAN MINUMAN BERALKOHOL DI KECAMATAN PANGKALAN KERINCI KABUPATEN PELALAWAN TAHUN 2020 - Novi Delvayanti; Erman Muchtar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Essay this aim for knowing how role Unit Police Civil Service Administration (SATPOL PP) on the sale of alcoholic beverages in the District Pangkalan Kerinci, Pelalawan Regency and the obstacles or obstacles experienced Satpol PP in Supervision of Alcoholic Drinks in Pangkalan Kerinci District districts Pelalawan. Drink alcoholic could bother peace and order general, this is Duty from Unit Police civil servant Soldier for maintain peace and order common in society.This study uses a qualitative approach and the type of descriptive data. The data used in this research are primary and secondary data, primary data through interviews with several sources and secondary data in the form of documents document or data which Writer take in office Satpol PP related drink alcoholic. Collection data via interview, observation and documentation.The results of the study show that the Satpol PP has carried out its role as a law enforcement officer tasked with maintaining peace and order general wrong the only one drink alcoholic to public in districts Base Kerinci districts Pelalawan, However from results raid which conducted there are still many stalls/kiosks selling alcoholic beverages to the public with evidence of the findings of alcoholic beverages, every Satpol PP conducts raid. This is due to community factors, law enforcement and the law alone. The form of supervision carried out by Satpol PP is direct supervision and no live. Keywords : Role Satpol PP, Supervision, drinks Alcoholic